Effects of Inflation under Fuzziness and Some Applications - Kahraman, Cengiz; Demirel, Tufan; Demirel, Nihan (SPRINGER-VERLAG BERLIN, 2008)
This chapter presents the ways of incorporating the parameter fuzzy inflation to the engineering economy analyses. Inflation is a financial parameter difficult to estimate. The fuzzy set theory gives us the possibility of converting linguistic expressions about inflation estimates to numerical values. In the chapter, discounted cash flow techniques including these fuzzy expressions and some numerical examples are given. The obtained results show the interval of the worst and the best possible outcomes when fuzzy inflation rates are taken into account.
Keywords: FUZZY; Computer Science; Mathematics